English Language Lecturers’ Attitudes Towards E-learning in the Context of Higher Education Institutions (HEIs) - Ali Zendah, Ali Abedlqader (Pusdikra Publishing, 2025)
The adoption of e-learning is often deemed essential during emergencies in the Gaza Strip. As a result, Many Higher Education Institutions (HEIs) are compelled to transition their classrooms to online delivery. This study, therefore, attempted to investigate the attitudes towards e-learning held by the English Department faculty members at five HEIs in the Gaza Strip-Palestine. The data collection instrument used in this research was the Test of e-Learning Related Attitudes (TeLRA) scale. The collected data were analyzed through means and percentages using SPSS v20 statistical package. The findings show that the participants hold mildly favourable attitudes towards e-learning. It was speculated that lecturers holding mildly favourable attitudes towards e-learning rather than strongly favourable attitudes may be attributed to the lack of training and some other difficulties which may hinder the successful implementation of e-learning in the Gaza Strip HEIs. It is then recommended that training and professional development on e-learning need to be provided to the lecturers in order to raise their awareness of e-learning and its benefits. Further research on lecturers’ attitudes towards e-learning and the difficulties they may encounter while adopting e-learning is essential. Such research may enable lecturers to become aware of their attitudes towards e-learning. It may also help educators and other stakeholders find ways to overcome these difficulties, ultimately supporting the successful implementation of e-learning in the context of the Gaza Strip HEIs.